Contradictory Effect of Notch1 and Notch2 on Phosphatase and Tensin Homolog and its Influence on Glioblastoma Angiogenesis: - Shabani, Mostafa; Taghvaei Javanshir, Hamid; Bereimipour, Ahmad; Ebrahimi Sadrabadi, Amin; Jalili, Arsalan; Nayernia, Karim (Galen Medical Journal, 2021)
Many genes induce angiogenesis in tumors, and among them, Notch family genes have received particular attention due to their extensive network of connections with other genes active in this function. Suppression of angiogenic signaling has been studied in various cancers, confirming Notch’s fundamental and extensive role. According to studies, four Notch genes work independently with many genes such as vascular endothelial growth factor, phosphatase and tensin homolog, Phosphoinositide 3-kinase/Akt, and matrix metalloproteinases, and so many other genes, as well as proteins (such as hypoxia-inducible factor-1 alpha) significantly affect tumor angiogenesis. Notch1 regular activity in a healthy person causes angiogenesis in body tissues, controlled by normal Notch2 activity. However, in many cases of glioblastoma, whether on patients or tumor xenografts or in vivo models, a mutation in one of these two essential genes or at least one of the genes and proteins that affected by them can cause better angiogenesis in hypoxic conditions and lead to become an invasive tumor. In this review, we examined the contrasting activity of Notch1 and Notch2 and the signaling cascade that each generates in the angiogenesis of glioblastoma, the most invasive cancer of the central nervous system. [GMJ.2021;10:e2091]